Toward quieter and more efficient supersonic flight: multi-objective optimization of a Bell-Shaped Lift Distribution wing SSBJ - Bonavolontà, Giordana; Manoj, Anirudh; Villena Munoz, Cristina; Tajesh Chilukuri, Sai; Lawson, Craig P.; Riaz, Atif (American Institute of Aeronautics and Astronautics (AIAA), 2024)
The optimization for low drag and boom of a new promising supersonic aircraft concept is presented in this paper. The Bell-Shaped Lift Distribution wing concept by Prandtl has been explored by the authors to design and optimize a supersonic business jet. This historical concept, known to be a theoretical solution for minimum induced drag wing, has been applied to redesign the SENECA E-19 Supersonic business jet wing. After having demonstrated that a bell span loading operates as intended in the supersonic regime, the configuration so designed has been optimized for low drag and boom by varying fuselage and tail design parameters. In addition, different combinations of engine positions have been also investigated within the optimization loop. The NSGA-II genetic algorithm has been chosen to carry out the multi- objective optimization. Low-to-medium fidelity numerical methods have been implemented to obtain the aerodynamic solution, while in-house multi-level of fidelity tool based on well-known methods has been used to perform sonic boom assessment. Take-off airframe noise assessment has been also performed on the final configuration resulting from optimization. The final configuration shows 6 % increase in aerodynamic efficiency and 7 % in boom with respect to the baseline.